Bioinformatics of genome evolution: from ancestral to modern metabolism Phylogenomics and comparative genomics to understand microbial evolution - Fondi, Marco (Premio Tesi di Dottorato, 2011)
Bioinformatics, that is the interdisciplinary field that blends computer science and biostatistics with biological and biomedical sciences, is expected to gain a central role in next feature. Indeed, it has now affected several fields of biology, providing crucial hints for the understanding of biological systems and also allowing a more accurate design of wet lab experiments. In this work, the analysis of sequence data has be used in different fields, such as evolution (e.g. the assembly and evolution of metabolism), infections control (e.g. the horizontal flow of antibiotic resistance), ecology (bacterial bioremediation).